Psychophysical and Electrophysiological Evidence for Enhanced Pain Facilitation and Unaltered Pain Inhibition in Acute Low Back Pain Patients - Vuilleumier, Pascal Henri (2017)
The aim of this case-control study was to examine differences in neural correlates of pain facilitatory and inhibitory mechanisms between acute low back pain (LBP) patients and healthy individuals. Pressure pain tolerance, electrical pain detection thresholds, pain ratings to repetitive suprathreshold electrical stimulation (SES) and conditioned pain modulation (CPM) were assessed in 18 patients with acute LBP and 18 healthy control participants. Furthermore, event-related potentials (ERPs) in response to repetitive SES were obtained from high-density electroencephalography. Results showed that the LBP group presented lower pressure pain tolerance and higher pain ratings to SES compared with the control group. Both groups displayed effective CPM, with no differences in CPM magnitude between groups. Both groups presented similar reductions in ERP amplitudes during CPM, but ERP responses to repetitive SES were significantly larger in the LBP group. In conclusion, acute LBP patients presented enhanced pain facilitatory mechanisms, whereas no significant changes in pain inhibitory mechanisms were observed. These results provide new insight into the central mechanisms underlying acute LBP. Perspective: This article present evidence that acute LBP patients show enhanced pain facilitation and unaltered pain inhibition compared with pain-free volunteers. These results provide new insight into the central mechanisms underlying acute LBP.